Acerca del renovado interés por Karl Polanyi - Subirats, Joan (Sobre o interesse renovado de Karl Polanyi., 2014)
¿Cómo es posible que un libro escrito hace setenta años despierte hoy un renovado interés y que sirva para hacer mejores diagnósticos sobre la crisis económica y sus posibles alternativas? En este texto trataremos de dar respuesta a este interrogante, mostrando los elementos que hacen de la obra de Polanyi un buen punto de partida para observar la crisis de legitimidad política y los problemas de relación entre economía de mercado y sistema político. La crítica de Polanyi a la naturalización de la economía de mercado es hoy plenamente actual. (Spanish)
Political Science
Keywords: bens comuns; bienes comunes; capitalismo; crises econômica; crisis económica; economia de mercado; economía de mercado; relaciones estado y sociedad; relações de estado e sociedade

Género y cuidados: respuestas sociales e institucionales al surgimiento de la sociedad de mercado en el contexto europeo - Carbonell Esteller, Montserrat; Gálvez Muñoz, Lina; Rodríguez Modroño, Paula (GENDER AND CARE: SOCIAL AND INSTITUTIONAL ANSWERS TO THE DEVELOPMENT OF THE MARKET ECONOMY IN EUROPE., 2014)
This article examines from a care approach the social and institutional responses to the development of the market economy in the European context. Studying this long period -which Polanyi called the double movement- is relevant because it constitutes the historical process by which the interests of the market, the logic of profits and its social and scientific naturalization come to dominate. Since then, the importance of care work in people's life, the reproduction of the labour force, and the provision of welfare and social insurance have been ignored. Until very recently, historical analyses have focused on the emergence of the Welfare State, regardless of how the state's answers interacted or modeled with other spheres of welfare provision, especially the family through women's unpaid work. The article focuses on the European experience and the period analyzed comprehends the disintegration of communal and assistance care with the Old Regime Crisis, the development of charity and associations as solutions to the inhibition of the Liberal State in the 19th century -solutions that were limited and insufficient, leading to the state assumption of the care and assistance functions, embryo of the development of later Welfare States after World War II. (English)
Economics
Keywords: capitalismo liberal; care; cuidados; estados del bienestar; gender; género; liberal capitalism; modelos asistenciales pre-industriales; pre-industrial mutual aid regimes; welfare state

Actualidad de la crítica de Karl Polanyi a la sociedad de mercados - Maya Ambía, Carlos Javier (Política y Cultura, 2014)
Karl Polanyi's critique of market society is a very powerful tool for understanding our current social reality. It helps us to formulate a creative and purposeful proposal that contributes to build a just, equitable, and more humane society, that would be committed to the future life on the planet. A comparison between the society criticized by Polanyi and ours, leads us to discover the validity of his basic concepts and his method for the preparation of a new critical discourse that not only takes advantage of the legacy of the author, but also expands, clarifies and updates it. (English)
Sociology
Keywords: crítica social; doble movimiento; double movement; market society; mercado autorregulado; self-regulated market; social critique; sociedad de mercado

Los conceptos más importantes en el trabajo de Karl Polanyi y su relevancia contemporánea - Polanyi Levitt, Kari (Economía y Desarrollo, 2014)
El artículo se centra en la vida y obra del historiador Karl Polanyi, quien escribió el libro "La Gran Transformación", en 2014 y también discute la investigación realizada sobre la vida económica de las sociedades primitivas por Polanyi.
Economics; Development Studies
Keywords: Great Transformation; The (Book); primitive societies

Crisis del modelo neoliberal, hacia una planificación regional. Un aporte polanyiano - Valderrama Saud, Paula (Crisis of the Neoliberal Model; Towards Regional Planning - a Polanyian Contribution., 2014)
Using Karl Polanyi's analytical instrument, I argue that the current withdrawal of the industrialized powers and the emergence of alternative policies in Latin America are determined by the crisis of the neoliberal model. The polarity between democracy and the market, observed since the beginnings of liberal capitalism, has deepened since the inter-war period due to the appearance of so-called "mass democracy." Since that period, foreign policies of industrialized countries have derived from social conflict caused by this polarity. Current neoliberalism, which favors the limitation of democracy in favor of the self-regulating global market, is a system that contains inherent contradictions on financial and socio-political levels. These contradictions are the cause of the current crisis in the United States and the European Union, a crisis that favors the beginning of a new era characterized by greater regional planning and a plurality of development paths. (English)
Economics
Keywords: European Union; Latin America; crisis; democracia; democracy; globalization; government policy; market; mercado; neoliberalism; neoliberalismo; planificación regional; regional planning